Altruism and egoism in the motivation of volunteering - Pokhomova, Alesya A. (Journal of the Belarusian State University. Sociology, 2023)
In the article, the author analyses the phenomenon of volunteering through the prism of altruistic and egoistic motivation. The essence of the social phenomenon under consideration is the implementation of a few key principles in the implementation of activities: voluntariness, focus on the welfare of others, unselfishness. These principles are closely related to the motivation of a volunteer as a social subject. The role of volunteering in social development is recognised internationally. The task set before the world community is to further promote the development of the volunteer movement among different socio demographic groups. The task is feasible if we have information about the motivation of volunteering and about external factors that facilitate or hinder the development of volunteerism at the local, national and international levels. The purpose of the research work was to consider the advantages of an interdisciplinary approach in the study of altruism and egoism, which underlie the motivation of volunteer activity. In the article, altruism and egoism are analysed from the standpoint of biological and social determinism.